2007
DOI: 10.4321/s1130-01082007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Células estrelladas hepáticas y estrés oxidativo

Abstract: RESUMENLa fibrosis hepática ocurre en la lesión hepática crónica y se caracteriza por la producción excesiva y el depósito de componentes de la matriz extracelular (MEC), fundamentalmente de colágeno de tipo I. Las células estralladas hepáticas (CEH) son las responsables de la producción excesiva de matriz extracelular durante la fibrosis. La activación de las CEH, constituye el paso fundamental del desarrollo de la fibrosis hepática y está mediada por citoquinas específicas y especies reactivas de oxígeno (ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Overexpression of MMP2 seemed strikingly associated with HCC because MMP2 in the tumor is mainly responsible for the fibrogenesis [ 25 ]. As reported, hepatic stellate cells, acting as main connective tissue cells in the liver, could be activated by oxidative stress and then produce extracellular matrix which is essential for normal growth and differentiation of cells after liver damage [ 26 ]. Our result suggests that oxidative stress in HCC not only directly affects the progression of HCC, but also interacts with other events to modulate HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MMP2 seemed strikingly associated with HCC because MMP2 in the tumor is mainly responsible for the fibrogenesis [ 25 ]. As reported, hepatic stellate cells, acting as main connective tissue cells in the liver, could be activated by oxidative stress and then produce extracellular matrix which is essential for normal growth and differentiation of cells after liver damage [ 26 ]. Our result suggests that oxidative stress in HCC not only directly affects the progression of HCC, but also interacts with other events to modulate HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are chemically reactive molecules produced during oxygen-related reactions. When the liver is attacked by harmful stimulations, hepatocytes, Kupffer cells, and HSCs themselves will produce large amounts of ROS [33,34], which react directly with intracellular lipids, proteins, and DNA, furtherly causing cell damage and death. Moreover, ROS can also activate HSCs through lipid peroxidation on the cell surface, leading to liver fibrosis.…”
Section: The Role Of Oxidative Stress In Liver Fibrosismentioning
confidence: 99%
“…Furthermore, ROS can specifically activate signaling pathways in HSC and LSEC, promoting fibrogenesis and increasing vascular tone. Particularly, in HSC, it has been suggested that ROS can trigger c-Jun N-terminal kinase (JNK), NFκB, and TGF-β signaling pathways, increasing the expression of collagen and other ECM components as well as pro-inflammatory mediators [ 48 , 49 , 50 , 51 ]. However, LSEC are probably the most sensitive liver cell type to oxidative stress.…”
Section: Major Contributors Of Acld Pathophysiologymentioning
confidence: 99%